Long-term outcome of hamstring lengthening versus transfer and the role of biceps femoris lengthening in patients with spastic diplegia and dynamic knee flexion in gait. (December 2022) - Do, Patrick; Feng, Jing; Sussman, Michael D
Background: Orthopedic treatment of flexed-knee gait consists of hamstring lengthening along with surgery at other levels. Transfer of the semitendinosus (hamstring transfer) was introduced to avoid increase of anterior pelvic tilt as well as reduce risk of recurrence. Methods: We retrospectively assessed children with spastic cerebral palsy and flexed-knee gait pre-operatively, 1 year post-operatively, and at a minimum of 7 years post-operatively. Results: The 39 patients were a mean 9.4 ± 3.4 years at the time of surgery, 20 subjects underwent hamstring transfer, and 19 subjects had hamstring lengthening with mean follow-up 9.1 years. Passive range of motion improved initially, but regressed at long term. Dynamic minimum knee flexion in stance decreased in both groups at the first post-operative study, and was maintained at final follow-up in 64-67% of patients. There was a small increase in anterior pelvic tilt at the 1-year follow-up which subsequently decreased to less than pre-operative in the hamstring lengthening group but remained mildly increased (5°) in the hamstring transfer group at final follow-up. Success in correcting stance knee flexion of the entire group was 69% of the Gross Motor Function Classification System grades I and II and 60% of the Gross Motor Function Classification System grade III subjects. Gait profile Score and sagittal knee Gait Variable Score both showed clinically important improvement after surgery and was mostly maintained long term for both groups. Lateral hamstring lengthening was beneficial in more severe patients, with minimal risk of adverse effects. Conclusion: Hamstring surgery as part of single event multi-level surgery (SEMLS) is effective in correcting flexed-knee gait in 60%–70% of patients with minimal effect on anterior pelvic tilt. There was no added advantage to hamstring transfer. Biceps Femoris lengthening may be beneficial and without significant additional risk. Level of evidence: level III.